New Construction and New Error Bounds for (0, 2, 4) Lacunary Interpolation By Six Degree Spline - Karwan Jwamer (Al-Rafidain Journal of Computer Sciences and Mathematics, 2011)
The object of this paper obtains the existence, uniqueness and upper bounds for errors of six degree splines interpolating the lacunary data (0, 2, 4). We also show that the changes of  the boundary conditions and the class of spline functions has a main role in minimizing the upper bounds for error in lacunary interpolation problem. For this reason, in the construction of our spline function which interpolates the lacunary data (0, 2, 4). We changed the boundary condition and the class of spline functions which are given by [4] from first derivative to third derivative and the class of spline function from   to   .